Land-use change, nutrition, and gender roles in Indonesian farm households - Daniel Chrisendo; Vijesh V. Krishna; Hermanto Siregar; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2019)
Many tropical countries are experiencing massive land-use change with profound environmental and socioeconomic implications. In Indonesia, oil palm cultivation is rapidly expanding at the expense of more traditional agricultural crops and forest land. While environmental effects of the oil palm boom were analyzed in many studies, much less is known about social effects. Here, we analyze how oil palm cultivation by smallholder farmers influences nutrition through changing income, gender roles, and other possible mechanisms. The analysis uses panel data collected in Jambi Province, Sumatra, one of the hotspots of Indonesia's recent oil palm boom. Regression models show that oil palm cultivation has positive effects on different indicators of nutrition and dietary quality. These effects are primarily channeled through income gains that improve smallholders' access to nutritious foods from the market. Oil palm requires less family labor than traditional crops, so a switch to oil palm could potentially free labor for off-farm economic activities. We find that oil palm cultivation is positively associated with off-farm employment of male but not female household members, which may be related to unequal opportunities. Independent of oil palm cultivation, female off-farm employment has positive nutrition effects, even after controlling for total household income.
urn:nbn:de:gbv:7-webdoc-3989-2
Keywords: 330; oil palm; smallholder livelihoods; gender roles; female empowerment; nutrition; dietary quality